Leg stiffness of older and younger individuals over a range of hopping frequencies. Issue 2 (April 2015) - Hobara, Hiroaki; Kobayashi, Yoshiyuki; Yoshida, Eiichi; Mochimaru, Masaaki
Abstract: The purpose of this study was to compare spring-mass behavior between older and younger individuals at a range of hopping frequencies. A total of 14 elderly and 14 young subjects performed in-place hopping in time with a metronome at frequencies of 2.2, 2.6, and 3.0 Hz. Using a spring-mass model, leg stiffness was calculated as the ratio of maximum ground reaction force to maximum center of mass displacement at the middle of the stance phase during ground contact. The lower extremities of both groups behaved like a simple spring-mass system at all three hopping frequencies. Further, statistical analysis revealed the existence of a significant interaction between hopping frequency and age group on leg stiffness. These results suggest that the sensitivity of leg stiffness to accommodate for variations in hopping frequency is likely to differ between elderly and young individuals.